Clinical characteristics and risk factors for 30-day mortality in esophageal cancer patients with upper gastrointestinal bleeding: a multicenter study - Lu, Sz-Wei; Pai, Chu-Pin; Yang, Ting-Hao; Lu, Jian-Xun; Hsiao, Chien-Han; Yen, Chieh-Ching (Frontiers in Oncology, 2023)
Background: Esophageal cancer is a highly malignant neoplasm with poor prognosis. Of its patients, upper gastrointestinal bleeding (UGIB) is one of the most challenging and threatening conditions in the emergency department (ED). However, no previous studies have analyzed the etiologies and clinical outcomes in this specific population. This study aimed to identify the clinical characteristics and risk factors for 30-day mortality in esophageal cancer patients with UGIB. Methods: This retrospective cohort study enrolled 249 adult patients with esophageal cancer presenting with UGIB in the ED. Patients was divided into the survivor and non-survivor groups, and their demographic information, medical history, comorbidities, laboratory parameters, and clinical findings were recorded. The factors associated with 30-day mortality were identified using Cox's proportional hazard model. Results: Among the 249 patients in this study, 30-day mortality occurred in 47 patients (18.9%). The most common causes of UGIB were tumor ulcer (53.8%), followed by gastric/duodenal ulcer (14.5%), and arterial-esophageal fistula (AEF) (12.0%). Multivariate analyses indicated that underweight (HR = 2.02, p = 0.044), history of chronic kidney disease (HR = 6.39, p < 0.001), active bleeding (HR = 2.24, p = 0.039), AEF (HR = 2.23, p = 0.046), and metastatic lymph nodes (HR = 2.99, p = 0.021) were independent risk factors for 30-day mortality. Conclusions: The most common cause of UGIB in esophageal cancer patients was tumor ulcer. AEF, accounting for 12% of UGIB in our study, is not an uncommon cause. Underweight, underlying chronic kidney disease, active bleeding, AEF, and tumor N stage > 0 were independent risk factors for 30-day mortality.